1-Benzoylmethyl-3-(2-thienylmethyl)-4-(2-thienylmethyleneamino)-1H-1,2,4-triazol-5(4H)-one - Tanak, Hasan (International Union of Crystallography, 2010)
In the title compound, C(20)H(16)N(4)O(2)S(2), one of the thiophene rings is disordered [occupancy ratio 0.710 (4):0.290 (4)] and the disorder is of the flip type. An intramolecular C—H⋯O hydrogen bond generates a six-membered ring with an S(6) motif.